Diametric calix[6]arene-based phosphine gold(I) cavitands - Giovanardi, Gabriele; Secchi, Andrea; Arduini, Arturo; Cera, Gianpiero (Beilstein Journal of Organic Chemistry, 2022)
We report the synthesis and characterization, in low polarity solvents, of a novel class of diametric phosphine gold(I) cavitands characterized by a 1,2,3-alternate geometry. Preliminary catalytic studies were performed on a model cycloisomerization of 1,6-enynes as a function of the relative orientation of the bonded gold(I) nuclei with respect to the macrocyclic cavity.
Keywords: 1,2,3-alternate conformation; calix[6]arenes; gold(I) catalysis; phosphines

(untitled) - Kaya, Z.; Bentouhami, E.; Pelzer, K.; Armspach, D. (Coord. Chem. Rev., 2021)

(untitled) - Olivo, G.; Capocasa, G.; Del Giudice, D.; Lanzalunga, O.; Di Stefano, S. (Chem. Soc. Rev., 2021)

(untitled) - Gramage-Doria, R.; Armspach, D.; Matt, D. (Coord. Chem. Rev., 2013)

Phosphorus(III) Ligands in Homogeneous Catalysis: Design and Synthesis - Kamer, P. C. J.; van Leeuwen, P. W. N. M. (John Wiley & Sons, 2012)

(untitled) - Orton, G. R. F.; Pilgrim, B. S.; Champness, N. R. (Chem. Soc. Rev., 2021)

(untitled) - Shet, H.; Parmar, U.; Bhilare, S.; Kapdi, A. R. (Org. Chem. Front., 2021)

(untitled) - Matt, D.; Harrowfield, J. (ChemCatChem, 2021)

(untitled) - Sémeril, D.; Matt, D. (Coord. Chem. Rev., 2014)

(untitled) - Schöttle, C.; Guan, E.; Okrut, A.; Grosso-Giordano, N. A.; Palermo, A.; Solovyov, A.; Gates, B. C.; Katz, A. (J. Am. Chem. Soc., 2019)

(untitled) - Karpus, A.; Yesypenko, O.; Boiko, V.; Poli, R.; Daran, J.-C.; Voitenko, Z.; Kalchenko, V.; Manoury, E. (Eur. J. Org. Chem., 2016)

(untitled) - Elaieb, F.; Hedhli, A.; Sémeril, D.; Matt, D. (Eur. J. Org. Chem., 2016)

(untitled) - Monnereau, L.; Sémeril, D.; Matt, D.; Toupet, L. (Adv. Synth. Catal., 2009)

(untitled) - Sémeril, D.; Matt, D.; Toupet, L. (Chem. – Eur. J., 2008)

(untitled) - Chavagnan, T.; Sémeril, D.; Matt, D.; Toupet, L. (Eur. J. Org. Chem., 2017)

(untitled) - Chavagnan, T.; Sémeril, D.; Matt, D.; Harrowfield, J.; Toupet, L. (Chem. – Eur. J., 2015)

(untitled) - El Moll, H.; Sémeril, D.; Matt, D.; Toupet, L. (Adv. Synth. Catal., 2010)

(untitled) - El Moll, H.; Sémeril, D.; Matt, D.; Youinou, M.-T.; Toupet, L. (Org. Biomol. Chem., 2009)

(untitled) - Martín‐Torres, I.; Ogalla, G.; Yang, J.-M.; Rinaldi, A.; Echavarren, A. M. (Angew. Chem., Int. Ed., 2021)

(untitled) - Rusali, L. E.; Schramm, M. P. (Tetrahedron Lett., 2020)

(untitled) - Inoue, M.; Kamiguchi, S.; Ugawa, K.; Hkiri, S.; Bouffard, J.; Sémeril, D.; Iwasawa, T. (Eur. J. Org. Chem., 2019)

(untitled) - Ho, T. D.; Schramm, M. P. (Eur. J. Org. Chem., 2019)

(untitled) - Inoue, M.; Ugawa, K.; Maruyama, T.; Iwasawa, T. (Eur. J. Org. Chem., 2018)

(untitled) - Endo, N.; Inoue, M.; Iwasawa, T. (Eur. J. Org. Chem., 2018)

(untitled) - Schramm, M. P.; Kanaura, M.; Ito, K.; Ide, M.; Iwasawa, T. (Eur. J. Org. Chem., 2016)

(untitled) - Endo, N.; Kanaura, M.; Schramm, M. P.; Iwasawa, T. (Eur. J. Org. Chem., 2016)

(untitled) - Mitschke, B.; Turberg, M.; List, B. (Chem, 2020)

(untitled) - Mouarrawis, V.; Plessius, R.; van der Vlugt, J. I.; Reek, J. N. H. (Front. Chem. (Lausanne, Switz.), 2018)

(untitled) - Homden, D. M.; Redshaw, C. (Chem. Rev., 2008)

(untitled) - Cera, G.; Arduini, A.; Secchi, A.; Credi, A.; Silvi, S. (Chem. Rec., 2021)

(untitled) - Cera, G.; Giovanardi, G.; Secchi, A.; Arduini, A. (Chem. – Eur. J., 2021)

(untitled) - Cera, G.; Cester Bonati, F.; Bazzoni, M.; Secchi, A.; Arduini, A. (Org. Biomol. Chem., 2021)

(untitled) - Cera, G.; Bazzoni, M.; Arduini, A.; Secchi, A. (Org. Lett., 2020)

(untitled) - Bazzoni, M.; Zanichelli, V.; Casimiro, L.; Massera, C.; Credi, A.; Secchi, A.; Silvi, S.; Arduini, A. (Eur. J. Org. Chem., 2019)

(untitled) - Cera, G.; Bazzoni, M.; Andreoni, L.; Cester Bonati, F.; Massera, C.; Silvi, S.; Credi, A.; Secchi, A.; Arduini, A. (Eur. J. Org. Chem., 2021)

(untitled) - van Duynhoven, J. P. M.; Janssen, R. G.; Verboom, W.; Franken, S. M.; Casnati, A.; Pochini, A.; Ungaro, R.; de Mendoza, J.; Nieto, P. M. (J. Am. Chem. Soc., 1994)

(untitled) - Nieto-Oberhuber, C.; Paz Muñoz, M.; López, S.; Jiménez-Núñez, E.; Nevado, C.; Herrero-Gómez, E.; Raducan, M.; Echavarren, A. M. (Chem. – Eur. J., 2006)

(untitled) - Fürstner, A.; Morency, L. (Angew. Chem., Int. Ed., 2008)

(untitled) - Jiménez-Núñez, E.; Echavarren, A. M. (Chem. Rev., 2008)